COVID-19 Home Quarantine Accelerated the Progression of Myopia in Children Aged 7 to 12 Years in China - Ma, Mingming; Xiong, Shuyu; Zhao, Shuzhi; Zheng, Zhi; Sun, Tao; Li, Chunxia (Investigative ophthalmology & visual science, 2021)
To investigate the effect of home quarantine during the COVID-19 pandemic on myopia progression in children and its associated factors.PurposeTo investigate the effect of home quarantine during the COVID-19 pandemic on myopia progression in children and its associated factors.Myopic children aged 7 to 12 years with regular follow-up visits every half a year from April 2019 to May 2020 were included. Cycloplegic refraction was measured at baseline and at two follow-up visits. The first follow-up visit (visit 1) was conducted before the COVID-19 home quarantine, whereas the second (visit 2) was four months after the home quarantine. Myopia progression at visits 1 and 2 were compared. Factors associated with changes in myopia progression were tested with a multiple regression analysis.MethodsMyopic children aged 7 to 12 years with regular follow-up visits every half a year from April 2019 to May 2020 were included. Cycloplegic refraction was measured at baseline and at two follow-up visits. The first follow-up visit (visit 1) was conducted before the COVID-19 home quarantine, whereas the second (visit 2) was four months after the home quarantine. Myopia progression at visits 1 and 2 were compared. Factors associated with changes in myopia progression were tested with a multiple regression analysis.In total, 201 myopic children were enrolled. There was a significantly greater change in spherical equivalent at visit 2 (-0.98 ± 0.52 D) than at visit 1 (-0.39 ± 0.58 D; P < 0.001). Students were reported to have spent more time on digital devices for online learning (P < 0.001) and less time on outdoor activities (P < 0.001) at visit 2 than at visit 1. Children using television and projectors had significantly less myopic shift than those using tablets and mobile phones (P < 0.001). More time spent on digital screens (β = 0.211, P < 0.001), but not less time on outdoor activities (β = -0.106, P = 0.110), was associated with greater myopia progression at visit 2.ResultsIn total, 201 myopic children were enrolled. There was a significantly greater change in spherical equivalent at visit 2 (-0.98 ± 0.52 D) than at visit 1 (-0.39 ± 0.58 D; P < 0.001). Students were reported to have spent more time on digital devices for online learning (P < 0.001) and less time on outdoor activities (P < 0.001) at visit 2 than at visit 1. Children using television and projectors had significantly less myopic shift than those using tablets and mobile phones (P < 0.001). More time spent on digital screens (β = 0.211, P < 0.001), but not less time on outdoor activities (β = -0.106, P = 0.110), was associated with greater myopia progression at visit 2.Changes in behavior and myopic progression were found during the COVID-19 home quarantine. Myopic progression was associated with digital screen use for online learning, but not time spent on outdoor activities. The projector and television could be better choices for online learning.ConclusionsChanges in behavior and myopic progression were found during the COVID-19 home quarantine. Myopic progression was associated with digital screen use for online learning, but not time spent on outdoor activities. The projector and television could be better choices for online learning.